Nursing performance in pregnancy loss assistance (Research, Society and Development, 2023)
Objective: The objective of the present study is to evaluate nursing performance in assisting pregnant women with risk factors for pregnancy loss. Methodology: This is an integrative literature review study, with the aim of enabling the analysis of relevant research to support better decision-making in clinical practice and nursing care. In the final sample of the research, 05 articles were included through the investigation carried out, as they presented answers to the objectives of this review. Discussion: In the studies evaluated, a lack of assistance aimed at women in situations of fetal loss was noticed and observed, as there is still no priority attention to health actions, which can be identified in the scarcity of health activities aimed at this care. In this perspective, professionals who work in direct obstetric care for women in situations of fetal loss are included, as well as those who carry out their work in the maternal and child area, in maternity wards or in so-called rooming-in units. Among these, the role of the nurse stands out, a professional qualified to provide assistance through nursing care. Conclusion: Therefore, it is suggested that health professionals turn their attention to this type of case, providing actions, lectures, training courses, scientific studies, and the exchange of knowledge and especially life experiences, not only between health professionals, but between patient and professional.